Dynamic airway function during exercise in COPD assessed via impulse oscillometry before and after inhaled bronchodilators - Tiller, Nicholas B.; Cao, Min; Lin, Fang; Yuan, Wei; Wang, Chu-Yi; Abbasi, Asghar; Calmelat, Robert; Soriano, April; Rossiter, Harry B.; Casaburi, Richard; Stringer, William W.; Porszasz, Janos (Journal of applied physiology (1985), 2021)
This study provides a novel, mechanistic insight into dynamic airway function during exercise in COPD, before and after inhaled bronchodilators. The use of impulse oscillometry (IOS) to evaluate airway function is unique among exercise studies. We show strong correlations among IOS variables, dynamic hyperinflation, and shape-changes in the spontaneous expiratory flow-volume curve. This approach may aid in clinical assessment of airway function during exercise. Assessing airway function during exercise provides useful information regarding mechanical properties of the airways and the extent of ventilatory limitation in COPD. The primary aim of this study was to use impulse oscillometry (IOS) to assess dynamic changes in airway impedance across a range of exercise intensities in patients with GOLD 1–4, before and after albuterol administration. A secondary aim was to assess the reproducibility of IOS measures during exercise. Fifteen patients with COPD (8 males/7 females; age = 66 ± 8 yr; prebronchodilator FEV 1 = 54.3 ± 23.6%Pred) performed incremental cycle ergometry before and 90 min after inhaled albuterol. Pulmonary ventilation and gas exchange were measured continuously, and IOS-derived indices of airway impedance were measured every 2 min immediately preceding inspiratory capacity maneuvers. Test-retest reproducibility of exercise IOS was assessed as mean difference between replicate tests in five healthy subjects (3 males/2 females). At rest and during incremental exercise, albuterol significantly increased airway reactance (X 5 ) and decreased airway resistance (R 5 , R 5 –R 20 ), impedance (Z 5 ), and end-expiratory lung volume (60% ± 12% vs. 58% ± 12% TLC, main effect P = 0.003). At peak exercise, there were moderate-to-strong associations between IOS variables and IC, and between IOS variables and concavity in the expiratory limb of the spontaneous flow-volume curve. Exercise IOS exhibited moderate reproducibility in healthy subjects which was strongest with R 5 (mean diff. = −0.01 ± 0.05 kPa/L/s; ICC = 0.68), R 5 –R 20 (mean diff. = −0.004 ± 0.028 kPa/L/s; ICC = 0.65), and Z 5 (mean diff. = −0.006 ± 0.021 kPa/L/s; ICC = 0.69). In patients with COPD, exercise evoked increases in airway resistance and decreases in reactance that were ameliorated by inhaled bronchodilators. The technique of exercise IOS may aid in the clinical assessment of dynamic airway function during exercise. NEW & NOTEWORTHY This study provides a novel, mechanistic insight into dynamic airway function during exercise in COPD, before and after inhaled bronchodilators. The use of impulse oscillometry (IOS) to evaluate airway function is unique among exercise studies. We show strong correlations among IOS variables, dynamic hyperinflation, and shape-changes in the spontaneous expiratory flow-volume curve. This approach may aid in the clinical assessment of airway function during exercise.